2017
DOI: 10.1167/17.3.26
|View full text |Cite
|
Sign up to set email alerts
|

The Davida Teller Award Lecture, 2016

Abstract: Research in the Visual Development Unit on “dorsal stream vulnerability' (DSV) arose from research in two somewhat different areas. In the first, using cortical milestones for local and global processing from our neurobiological model, we identified cerebral visual impairment in infants in the first year of life. In the second, using photo/videorefraction in population refractive screening programs, we showed that infant spectacle wear could reduce the incidence of strabismus and amblyopia, but many preschool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 202 publications
(264 reference statements)
8
46
1
Order By: Relevance
“…Overall, high-level motion perception can be assumed to be substantially modulated by cognitive processes, e.g., predictions, motivation, attention, or memory, which help to assess and interpret the visual input. It has been suggested that the dorsal stream is particularly vulnerable during child development (Atkinson, 2017;Braddick, Atkinson, & Wattam-Bell, 2003). A corresponding vulnerability during aging still awaits clarification.…”
Section: Vulnerability Of Motion Perception On Different Processing Smentioning
confidence: 99%
“…Overall, high-level motion perception can be assumed to be substantially modulated by cognitive processes, e.g., predictions, motivation, attention, or memory, which help to assess and interpret the visual input. It has been suggested that the dorsal stream is particularly vulnerable during child development (Atkinson, 2017;Braddick, Atkinson, & Wattam-Bell, 2003). A corresponding vulnerability during aging still awaits clarification.…”
Section: Vulnerability Of Motion Perception On Different Processing Smentioning
confidence: 99%
“…The observation that Developmental Dyslexia (DD), Autism Spectrum Disorder (ASD), Intellectual Disability (ID), William's and Fragile X Syndrome share a deficit in global motion processing led to the formulation of the Dorsal Stream Vulnerability Hypothesis, by Braddick et al (2003). Since then, many studies have provided further support for the theory (Grinter et al, 2010;Atkinson, 2017) and extended it to include deficits in visuomotor spatial integration for planning actions and attention (Atkinson, 2017). Indeed, epidemiological evidence (Carroll and Owen, 2009;Moskvina et al, 2009) has supported shared symptomology and clustering of neurodevelopmental disorder (NDD) symptoms (DSM-5, American Psychiatric Association, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…MD form stimuli activate the classic motion area MT+, regions in the intraparietal cortex of the dorsal stream, and also regions in the inferior temporal cortex and lateral occipital cortex of the ventral stream (Gulyas, Heywood, Popplewell, Roland, & Cowey, 1994;Meier, Partanen, & Giaschi, 2018). Motion sensitivity continues to improve into the school-age years and the age of maturation to adult-like performance depends on spatial and temporal stimulus parameters (Giaschi & Regan, 1997;Meier & Giaschi, 2014, 2017Parrish, Giaschi, Boden, & Dougherty, 2005;Schrauf, Wist, & Ehrenstein, 1999). Because the performance of young children (4-6 years) is immature for MD form stimuli using slow (<1 deg/s) but not fast (5 deg/s) signal dot speeds (Hayward, Truong, Partanen, & Giaschi, 2011), the current study employed a stimulus with a slow speed (0.1 deg/s) to track development as a function of age.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that performance on a global motion task can be used as an index of overall dorsal stream function (Braddick et al, 2016;Chakraborty et al, 2017;Thompson et al, 2017). Following this line of thought, research has shown that children with various neurodevelopmental disorders, such as autism, attention deficit hyperactivity disorder, dyslexia, amblyopia, or preterm birth have impaired sensitivity to motion, which has led to the 'dorsal-stream vulnerability' hypothesis (reviewed in Atkinson, 2017; but also see Grinter, Maybery, & Badcock, 2010).…”
Section: Introductionmentioning
confidence: 99%